Stiff-person syndrome mimic secondary to hypopituitarism: a case report and literature review - Zheng, Menghan; Cui, Bo; Liu, Junqi; Duan, Huanli; Wang, Wei; Li, Haifeng; Lu, Lu (Frontiers in Endocrinology, 2025)
IntroductionFlexion contracture has been reported to be associated with hypopituitarism and hypoadrenalism. We reported a case of a patient who presented with stiff-person syndrome (SPS) mimic secondary to prolactinoma-associated hypopituitarism.MethodsA case of SPS mimic secondary to hypopituitarism was reported. Literature review identified six additional reported SPS mimic cases associated with hypopituitarism until July 2025. We summarized the etiologies, clinical features, and therapeutic revelations of these cases.ResultsWe described a patient who developed progressive rigidity of the lower limbs and trunk with painful spasms precipitated by sensory stimuli for 6 months, initially suspected as SPS. Investigations indicated hypopituitarism secondary to prolactinoma, and hormone replacement therapy showed a favorable clinical response. The literature review showed six similar cases of SPS mimic secondary to hypopituitarism. The underlying causes were attributed to pituitary mass and Sheehan’s syndrome for male and female patients, respectively. Flexion contracture and painful spasms predominated the typical pictures and responded satisfactorily to glucocorticoid supplementation.ConclusionsSPS mimic is a rare neurological manifestation secondary to hypopituitarism, typically hypoadrenalism. Our report raises awareness of this potential complication to promote early hormonal evaluation and prompt glucocorticoid replacement therapy. Further studies are warranted to elucidate the mechanism between adrenal deficiency and neurological manifestations.